1995
DOI: 10.20955/wp.1995.013
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Banks Disappear: The Determinants of U.S. Bank Failures and Acquisitions

Abstract: This paper examines the determinants of individual bank failures and acquisitions in the United States during 1984-1993. We use bank-specific information suggested by examiner CAMELrating categories to estimate competing-risks hazard models with time-varying covariates. We focus especially on the role of management quality, as reflected in alternative measures of xefficiency and find the inefficiency increases the risk of failure, while reducing the probability of a bank's being acquired. Finally, we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
179
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(190 citation statements)
references
References 10 publications
9
179
1
1
Order By: Relevance
“…Finally, as Rawcliffe and Andrews (2003) point out bigger banks (in terms of absolute size of a bank's equity) are more likely to be important to their domestic economics, increasing the probability to receive external support, if required, hence decreasing their risk of default. Banks with higher return on equity and net interest margin, also receive higher ratings that is consistent with prior studies such as the ones of Poon et al (1999) who find profitability to be positively related to higher ratings in the case of Moody's, and Wheelock and Wilson (2000) who reveal a statistically significant and negatively relation between profitability and probability of failure. NIM appears to be more important in characterizing banks that are assigned below D ratings, with weights that equal 38.35% and 33.06% in U 4 , and U ∼4 accordingly, rather than banks with higher ratings.…”
Section: Resultssupporting
confidence: 87%
“…Finally, as Rawcliffe and Andrews (2003) point out bigger banks (in terms of absolute size of a bank's equity) are more likely to be important to their domestic economics, increasing the probability to receive external support, if required, hence decreasing their risk of default. Banks with higher return on equity and net interest margin, also receive higher ratings that is consistent with prior studies such as the ones of Poon et al (1999) who find profitability to be positively related to higher ratings in the case of Moody's, and Wheelock and Wilson (2000) who reveal a statistically significant and negatively relation between profitability and probability of failure. NIM appears to be more important in characterizing banks that are assigned below D ratings, with weights that equal 38.35% and 33.06% in U 4 , and U ∼4 accordingly, rather than banks with higher ratings.…”
Section: Resultssupporting
confidence: 87%
“…Wheelock and Wilson (2004) used a cross-sectional approach to examine 890 U.S. bank mergers between 1984 and 1993 and found that efficient banks are less likely to be acquired. Consistent with these findings, Akhigbe et al (2004) showed that the chances of a U.S. bank being acquired is higher if the bank is large and/or relatively less profitable, while an earlier study by Wheelock and Wilson (2000) found that banks with lower capital ratios are more likely to be acquisition targets. Collectively, these studies suggest an efficient market for corporate control.…”
Section: Geographic Diversificationmentioning
confidence: 64%
“…There is also a set of studies, including for the US, Kimura and Fujii (2003) for Japan and Esteve et al (2004) and Esteve and Mañez (2007) for Spain, that conclude that firms investing in R&D activities increase their likelihood of survival. However, Cefis and Marsili (2005) show that the ''innovation premium'' that positively affects firm survival stems mainly from firms investing in process 8 Other firm survival studies that explore competing risks specifications are, for example, Wheelock and Wilson (2000) and Mata and Portugal (2000). The former analyse acquisition and bankruptcy in the US banking sector and the latter distinguish between liquidation and divestiture in a sample of new foreign manufacturing firms.…”
Section: Internal Factorsmentioning
confidence: 99%